2014
DOI: 10.1007/s12288-014-0342-z
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of FVIII Inhibitors in Indian Haemophilia A Patients

Abstract: A serious complication of replacement therapy in patients with bleeding disorders is the development of 'inhibitors', particularly FVIII inhibitors in haemophilia A patients. This leads to an increase in the management cost, morbidity and mortality, especially post-operatively. The mechanism of FVIII inhibitor development is quite complex and it is difficult to predict inhibitor development, but a prompt and accurate diagnosis is critical as early therapy can save lives. The aim of this study was to screen pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
4
13
0
Order By: Relevance
“…A large Indian study of 1285 patients with hemophilia A found that only 6.07% of the patients had inhibitors, although there were remarkable regional variations (the highest prevalence was 20.99%). [35] We also found a higher prevalence of inhibitors among patients who were receiving recombinant factors, and this result agrees with the findings from our previous studies. [3638] …”
Section: Discussionsupporting
confidence: 93%
“…A large Indian study of 1285 patients with hemophilia A found that only 6.07% of the patients had inhibitors, although there were remarkable regional variations (the highest prevalence was 20.99%). [35] We also found a higher prevalence of inhibitors among patients who were receiving recombinant factors, and this result agrees with the findings from our previous studies. [3638] …”
Section: Discussionsupporting
confidence: 93%
“…In a previous study conducted in India, researchers found that 6.07% of patients exhibited inhibitors. However, the authors found significant variations among the various regions studied, with one region featuring a prevalence of 20.99% …”
Section: Discussionmentioning
confidence: 93%
“…There is a paucity of data regarding the prevalence of inhibitors in severe haemophilia A from low and middle income countries (LMIC) and from different races and ethnicities. A previous study that published data in this regard from India showed an overall prevalence of 6.07% with a varying distribution of 4.17%, 4.89%, 5.45% and 13.04% of inhibitors from Western, Eastern, Northern and Southern regions . Several of these studies were not comprehensively designed and have a tertiary centre referral bias.…”
Section: Introductionmentioning
confidence: 98%
“…A previous study that published data in this regard from India showed an overall prevalence of 6.07% with a varying distribution of 4.17%, 4.89%, 5.45% and 13.04% of inhibitors from Western, Eastern, Northern and Southern regions. 17 Several of these studies were not comprehensively designed and have a tertiary centre referral bias. In this study, we undertook a comprehensive community-based evaluation of severe haemophilia A patients to study the prevalence of inhibitors and its predisposing factors.…”
Section: Introductionmentioning
confidence: 99%